2020
DOI: 10.1002/smll.202002985
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of FeNi Bimetal Modified Covalent Organic Frameworks for Photoconversion of Anthropogenic CO2 into Widely Tunable Syngas

Abstract: Direct photoconversion of low‐concentration CO2 into a widely tunable syngas (i.e., CO/H2 mixture) provides a feasible outlet for the high value‐added utilization of anthropogenic CO2. However, in the low‐concentration CO2 photoreduction system, it remains a huge challenge to screen appropriate catalysts for efficient CO and H2 production, respectively, and provide a facile parameter to tune the CO/H2 ratio in a wide range. Herein, by engineering the metal sites on the covalent organic frameworks matrix, low‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…However, the production rate of syngas decreased slightly after 3 h reaction, probably caused by the partial deactivation of the photosensitizer after the prolonged reaction. 53 The apparent quantum efficiency (AQE) for syngas production under 420 nm single-wavelength irradiation was calculated to be 1.18%, which was competitive with that of most reported metal-modified COF-based photocatalytic systems under similar reaction conditions (Table S1†).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…However, the production rate of syngas decreased slightly after 3 h reaction, probably caused by the partial deactivation of the photosensitizer after the prolonged reaction. 53 The apparent quantum efficiency (AQE) for syngas production under 420 nm single-wavelength irradiation was calculated to be 1.18%, which was competitive with that of most reported metal-modified COF-based photocatalytic systems under similar reaction conditions (Table S1†).…”
Section: Resultsmentioning
confidence: 74%
“…Compared with COF-TVBT-Bpy, the PL intensity of Co@COF-TVBT-Bpy decreased remarkably, and the average fluorescence lifetime ( τ = 2.5 ns) was shorter than that of COF-TVBT-Bpy ( τ = 6.5 ns), suggesting that the incorporation of Co ions could restrain the recombination of photogenerated electron–hole pairs. 53 Transient photocurrent response measurements were performed under visible-light irradiation to explore the transfer efficiency of photogenerated electrons. The photocurrent generated by the two materials exhibited reproducible response without obvious attenuation, and Co@COF-TVBT-Bpy showed higher photocurrent response intensity compared with COF-TVBT-Bpy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, because of the crystalline and porous features, covalent organic frameworks (COFs) have attracted considerable attention in gas storage, catalysis, and photoelectric areas. [ 29–38 ] Particularly, integration of topologically identical and catalytically active building blocks into the porous extended structures could endow COFs to bridge a gap between homogeneous and heterogeneous catalysis. [ 39 ] Despite several COFs have been reported for CO 2 RR, the insulating nature usually leads to low current density and thus limits their application.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been found that the co-operative effect between the d-block elements such as Fe 51 and Ni 200 could feature in bimetallic active centres, which resulted in pronounced/improved photoreduction of CO 2 . Aiming towards it, very recently, Han et al 41 rationally customized a COF by integrating Fe/Ni metal sites over the surface, which was successfully utilized for photoreduction of less concentrated CO 2 into tuneable syngas (Fig. 10a–c).…”
Section: Photocatalysts For Syngas Productionmentioning
confidence: 99%
“…Herein, we have discussed and emphasized different photoactive materials including MOFs, 28,39 organic polymers, 21,[40][41][42] POMs, 43,44 LDHs, 45,46 metal oxides, 47,48 metal complexes, 49,50 and single atom metals 51,52 for CO 2 reduction into syngas and have thus briefly described their photocatalytic activities to rationalize the stream proportion of the syngas mixture i.e. CO/H 2 or H 2 /CO.…”
Section: Introductionmentioning
confidence: 99%